Looking after ourselves at work: the importance of being hydrated and fed. (6th February 2019) - Brennan, Peter A; Oeppen, Rachel; Knighton, John; Davidson, Mike
Abstract : Hospitals should remove any barriers to doctors eating and drinking during the working day